FACTORS AFFECTING THE DECISION TO PURCHASE BIO-ORGANIC FERTILIZER FOR RICE PRODUCTION IN THE MEKONG DELTA, VIETNAM - Le Canh DUNG; Nguyen Thanh NHIEN (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Using industrial bionitrogen fertilizer for crops is a new trend to improve the quality and value of agricultural products while helping to improve the soil environment and can completely replace traditional chemical nitrogen. Industrial bionitrogen fertilizer is gradually being produced and consumed in Vietnam and the Mekong Delta. However, the level of industrial bionitrogen fertilizer consumption is still limited for many reasons. This study interviewed 250 rice farmers in the Mekong Delta provinces who consumed industrial bionitrogen fertilizers, then used exploratory factor analysis to evaluate the influence of factors on their decisions of purchasing industrial bionitrogen fertilizer. The results show that there are at least 5 factors that have a positive impact on purchasing decisions, arranged according to their importance: consumer awareness, subjective standards, product quality, distribution system and sales promotion. On this basis, some policy implications and solutions have been proposed.